The Virtue of Being Underestimated: A Note on Discriminatory Contracts in Hidden Information Models - Wendelin Schnedler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
A standard hidden information model is considered to study the influence of the a priori productivity distribution on the optimal contract. A priori more productive (hazard rate dominant) agents work less, enjoy lower rents, but generate a higher expected surplus.
Keywords: D82; J71; 330; adverse selection; statistical discrimination; stochastic order relation